BIA-ALCL and Textured Breast Implants: A Systematic Review of Evidence Supporting Surgical Risk Management Strategies. (May 2021) - Nelson, Jonas A.; McCarthy, Colleen; Dabic, Stefan; Polanco, Thais; Chilov, Marina; Mehrara, Babak J.; Disa, Joseph J.
Abstract : Background: Breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) is a significant public health concern for women with breast implants. The increase in incidence rates underscores the need for improved methods for risk reduction and risk management. The purpose of this study was to perform a systematic review to assess surgical risk reduction techniques and analyze communication/informed consent practices in patients with textured implants. Methods: A systematic review of the literature was conducted in PubMed (legacy), Embase (Embase.com), and Scopus with four search strategies including key terms centered around breast reconstruction and BIA-ALCL. Results: A total of 571 articles were identified, of which 276 were included in the final review after duplicates were removed. After review, no articles were determined to fit the inclusion criteria of demonstrating data-driven evidence of BIA-ALCL risk reduction through surgical measures, demonstrating a significant lack of data on risk reduction for BIA-ALCL. Conclusions: Risk management for BIA-ALCL is an evolving area requiring additional investigation. Although removal of textured devices in asymptomatic patients is not currently recommended by the Food and Drug Administration, variability in estimates of risk has led many patients to electively replace these implants in an effort to decrease their risk of developing BIA-ALCL. To date, however, there is no evidence supporting the concept that replacing textured implants with smooth implants reduces risk for this disease. This information should be used to aid in the informed consent process for patients presenting to discuss management of textured breast implants.